2005
DOI: 10.1097/01.ajp.0000146165.15529.50
|View full text |Cite
|
Sign up to set email alerts
|

Oral Methadone for Chronic Noncancer Pain

Abstract: Oral methadone is used for various noncancer pain syndromes, at different settings and with no prescription pattern that could be identifiable. Starting, maintenance, and maximum doses showed great variability. The figure of 59% effectiveness of methadone should be interpreted very cautiously, as it seems overrated due to the poor quality of the uncontrolled studies and their tendency to report positive results. The utilization of oral methadone for noncancer pain is based on primarily uncontrolled literature.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…The effectiveness of the most commonly prescribed opioids for CNCP, including codeine, morphine, oxycodone and tramadol, has been evaluated in several systematic reviews (10)(11)(12)(16)(17)(18)(19)(20)(21)(22). The most common kinds of CNCP represented in these reviews were low back pain, osteoarthritis, and neuropathic pain.…”
Section: Effectiveness Of Opioids For Relieving Pain and Improving Fu...mentioning
confidence: 99%
“…The effectiveness of the most commonly prescribed opioids for CNCP, including codeine, morphine, oxycodone and tramadol, has been evaluated in several systematic reviews (10)(11)(12)(16)(17)(18)(19)(20)(21)(22). The most common kinds of CNCP represented in these reviews were low back pain, osteoarthritis, and neuropathic pain.…”
Section: Effectiveness Of Opioids For Relieving Pain and Improving Fu...mentioning
confidence: 99%
“…Methadone has traditionally been used in the management of opioid dependence. However, there is increasing interest in the repurposing of methadone as a cost-efficient treatment for neuropathic pain [6,7]. Morley, et al [8] reported the efficacy of oral methadone for the management of neuropathic pain in a double-blind randomized controlled crossover trial.…”
Section: Introductionmentioning
confidence: 99%
“…This syndrome is thought to be under-recognized, but is probably becoming more prevalent because of an increase in the use of narcotics for chronic nonmalignant painful disorders in United States (4,6, 10), and the paradoxical development of increased pain in those chronically taking opiates associated with maladaptive behaviors (11, 12). However, to our knowledge, there are no epidemiological data on the prevalence of NBS in the US community or elsewhere.…”
Section: Introductionmentioning
confidence: 99%